PENGARUH RASIO LIKUIDITAS, RASIO PROFITABILITAS, RASIO MANAJEMEN UTANG, DAN RASIO AKTIVITAS TERHADAP RETURN SAHAM - Nagari, Rosalia Septia; Yuana, Pusvita (Jurnal Management Risiko dan Keuangan, 2022)
The purpose of this study is to analyze the effects of liquidity ration profitability ratio, debt management ratio, and activity ratio on stock return. This explanatory research uses quantitative approach in explaining the relationship of a variable with the others. Secondary data compiled from the annual reports of food and beverages companies listed on the Indonesia Stock Exchange was used in this research. Using purposive sampling technique, nine companies that meet the criteria were selected as the sample. The hypotheses were tested based the multiple linear regression analysis. The independent variables in this study are liquidity ratio that was measured using Current Ratio (CR), profitability ratio that was measured using Return on Assets (ROA), debt management ratio that was measured using Debt-to-Equity Ratio (DER), and activity ratio that was measured using Total Assets Turnover (TATO). The dependent variable is stock return. This study finds that, in partial ways, there are insignificant effects of financial performance that was measured using CR, DER, and TATO on stock return and that there is a positive and significant effect of financial performance that was measured using ROA on stock return.